PENGARUH JUMLAH UANG BEREDAR DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Risky Meri Yosephina; Murtala Murtala (Jurnal Ekonomi Regional Unimal, 2019)
This study aimed to determine the effect of the money supply and population on economic growth in indonesia in the short and long term. This study used time series data from 1994 to 2017. The data analysis method used is the Auto Regressive Distributed Lagged (ARDL) approach. The results showed that all variables are stationary at the co-integrated in the long run. The model stability test results showed that the model used was stable. The results show that all variables were stationary at the co-integrated level in the long run. The model stability test results showed that the model used is stable. Partially, in the analysis of short-term money supply had a negative and significant effect on the economic growth in Indonesia, and the population had a positive and significant effect on the value of economic growth in Indonesia. In the long-term analysis, the money supply had a negative and significant effect on the economic growth in Indonesia, and the population had a positive and significant effect on the economic growth in Indonesia. The coefficient determination R2 was 91.56 percent.